2019
DOI: 10.3390/md17020134
|View full text |Cite
|
Sign up to set email alerts
|

Barrel Jellyfish (Rhizostoma pulmo) as Source of Antioxidant Peptides

Abstract: The jellyfish Rhizostoma pulmo, Macrì 1778 (Cnidaria, Rhizostomae) undergoes recurrent outbreaks in the Mediterranean coastal waters, with large biomass populations representing a nuisance or damage for marine and maritime activities. A preliminary overview of the antioxidant activity (AA) of R. pulmo proteinaceous compounds is provided here based on the extraction and characterization of both soluble and insoluble membrane-fractioned proteins, the latter digested by sequential enzymatic hydrolyses with pepsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 107 publications
(138 reference statements)
2
64
0
Order By: Relevance
“…The present work aimed to ascertain whether a "core" of bacteria can be found to be associated with the "sea lung" or "barrel" jellyfish, R. pulmo, in both the warmest and coldest periods of the year. This species has been recently proposed as a novel, "blue growth" resource for nutritional, nutraceutical, and other biotechnological applications [61,62,64,69]. Previous researches dealt with the impact of jellyfish mucus release and biomass decay on bacterioplankton growth and community composition [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work aimed to ascertain whether a "core" of bacteria can be found to be associated with the "sea lung" or "barrel" jellyfish, R. pulmo, in both the warmest and coldest periods of the year. This species has been recently proposed as a novel, "blue growth" resource for nutritional, nutraceutical, and other biotechnological applications [61,62,64,69]. Previous researches dealt with the impact of jellyfish mucus release and biomass decay on bacterioplankton growth and community composition [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using an ultra-light aerial survey, a remarkable R. pulmo outbreak characterized by over 48,000 ind/km 2 and a biomass assessment of ~300 t/km 2 was reported along the southwestern shores of the Gulf of Taranto [61]. Many jellyfish species, including R. pulmo, represent a potential exploitable source of bioactive compounds in nutritional, nutraceutical, cosmeceutical, and pharmacological applications on account of their high biomasses and their associated microbiome [62][63][64][65][66]. Taking advantage from ongoing research on the microbial assemblages associated to common Mediterranean jellyfish [22,39], the present study aimed to investigate the microbiome associated with different fractions (umbrella, oral arms, and secreted mucus) of jellyfish at the lowest sea surface temperature values (typically February in the Mediterranean [67]), and to compare it with that already described during the warmest months (July-August) from the same jellyfish species, R. pulmo, and locality in the Northern Ionian Sea (Gulf of Taranto, SE Italy) [39].…”
Section: Mar Drugs 2020 18 X For Peer Review 3 Of 28mentioning
confidence: 99%
“…Jellyfish collagen is a source of a great number of antioxidants. Recently, it was demonstrated that peptide fractions from R. pulmo collagen were able to prevent oxidative stress in HEKa cells treated with H 2 O 2 [136]. Moreover, collagen peptides exhibiting scavenging and antifatigue activities were identified in R. esculentum [137,138], as well as collagen hydrolysate with several activities (including superoxide anion-scavenging and melanogenesis-inhibitory activities) based on the capacity of the hydrolysate to chelate copper inhibiting the intracellular tyrosinase activity [139].…”
Section: Jellyfishmentioning
confidence: 99%
“…Rhizostoma pulmo (known as sea lung or barrel JF) was used here as model organism, since it is considered edible in some Asian countries [20] and it has also been recently considered one of JF species in setting up a possible new method to obtain a potential human food or food ingredients for European Countries [11,12,13]. The set of parameters proposed in this study should be applied and validated also for other abundant and putatively edible JF species in Mediterranean Basin (i.e., Aurelia aurita , Cotylorhiza tuberculata, Rhopilema nomadica , etc) suitable to be used as novel foods in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, recent research studies have reported that some JF species with outbreak-forming populations in the Mediterranean Sea have biochemical and textural features similar to edible Asiatic species [10,11,12]. These native JF species in the Mediterranean Sea seem to be good candidates as a new “local seafood product” characterized by nutraceutical features [10,13].…”
Section: Introductionmentioning
confidence: 99%